THE CORRELATION BETWEEN ACID FAST BACILLI OF THE INTENSIVE AND CONTINUATION PHASE IN PULMONARY TUBERCULOSIS PATIENTS’ CATEGORY 1 - Oki Nugraha Putra; Widyananda Kartikasari; Hardiyono _; Ana Khusnul Faizah (Jurnal Farmasi Sains dan Praktis, 2021)
Tuberculosis (TB) is a communicable disease caused by M. tuberculosis and known as Acid Fast Bacilli (AFB). The purpose of this study was to analyze the correlation between AFB at the end of the intensive phase and continuation phase and to analyze the variables that associated with sputum conversion at the end of continuation phase in pulmonary TB patient’s category I in several primary public health in Surabaya. This was an observational analytic with a retrospective cohort design. Data were collected by medical records of TB patients from January 2017 to December 2019. One hundred twenty-four of TB patients met the inclusion criteria with 69 male and 55 females, and mean of age was 44.09 ± 12.05 years old. The initial AFB was mostly 1+ (41%). There was a significant correlation between AFB at the end of intensive phase and continuation phase (p-value=0.000; r=0.657) by Kendal-Tau test. Age was significantly associated with sputum conversion at the end of continuation phase (p-value=0.022). The conclusion of this study that there was a significant correlation between AFB at the end of intensive phase and continuation phase